INTEGRATION OF EPISTEMOLOGY: MEDIEVAL ISLAMIC PERSPECTIVES ON THE HIERARCHY OF KNOWLEDGE, THE QUR’AN, AND PHILOSOPHY - Armalena Armalena; Syahrul Fadli; Mardianis Mardianis; Saifullah Saifullah; Riki Saputra (Journal International Dakwah and Communication, 2026)
Mainstream narratives often label the Medieval period as a time of global intellectual stagnation, whereas Islamic civilization actually recorded a golden age through the integration of theology, philosophy, and science, reaching its pinnacle. This study seeks to reconstruct the concept of knowledge (‘ilm) in the medieval Islamic tradition and to map the interrelation between the authority of revelation and rationality. The author applies a library research method with content analysis techniques on the thoughts of key figures such as Al-Farabi, Ibn Rushd (Averroes), and Ibn al-Haytham. The analysis identifies three fundamental points: first, medieval Islamic epistemology was holistic, eliminating the dichotomy between sacred and profane spheres; second, the Qur’an serves as an epistemological constitution that legitimizes empirical observation through the doctrine of the "Two Books" (Tadwini and Takwini); and third, philosophy and science are positioned as collective obligations (fardhu kifayah) consistent with the message of revelation. This study concludes that addressing the crisis of modern knowledge dichotomy requires a renewed adoption of the classical spirit of epistemological integration.